Performance of The Composite Electrode of Reduced Graphene Oxide Palm Oil Shell - Zinc Oxide (rGOCKS - ZnO) as a Chemical Oxygen Demand (COD) Sensor by Photoelectrocatalysis - Azis, Thamrin; Muzakkari, Muhammad Z.; Nurdin, Muh.; Maulidiyah, Maulidiyah; Muslia, Wa O.; Bijang, Catherina M.; Tahril, Tahril (Universitas Tadulako, 2023)
The preparation of reduced graphene oxide composite electrodes from palm shells (rGOCKS-ZnO) as a chemical oxygen demand (COD) sensor by photoelectrocatalysis has been successfully carried out. The preparation of rGOPS - ZnO electrodes by thermal reduction method and modified Hummer. The XRD results showed several peaks of rGOCKS - ZnO namely 23.287 º, 26.781 °, 29.889 °, 32.468 °, 35.109 °, 37.14 °, 39.822 °, 43.559 °, 47.927 °, and 48.537 °. SEM-EDX analysis reveals the surface of graphene sheets containing aggregates in the shape of small particles attached to graphene sheets. The results of the EDX analysis consisted of C 67.82 %, O. 19.2 %, Zn. 7.85 % and 5.13 % impurity. The CV and LSV tests showed that the rGOAK - ZnO electrode with a variation of 1 gram: 0.3 gram had a good response to the oxidation process under visible light. The profile tests of these organic dyes (methylene blue) in concentrations of 0.5 ppm, 1.0 ppm, 2.0 ppm, and 3.0 ppm were applied by Multi Pulse Amperometry (MPA). The performance of the rGOPS - ZnO electrode has been in determining the value of COD by photo electrocatalytic good sensitivity, linearity, limit of detection, repeatability, and service life. The COD value was determined using the rGOPS - ZnO electrode and obtained 2.97897 mg/LO2 close to the theoretical value.